THE USE OF MODIFIED T LYMPHOCYTES (CAR-T AND CAR-Treg) AS A STRATEGY FOR RESTORING IMMUNOLOGICAL TOLERANCE IN SEVERE FORMS OF SYSTEMIC LUPUS ERYTHEMATOSUS AND SYSTEMIC SCLEROSIS – ANALYSIS OF EFFICACY AND SAFETY IN THE LIGHT OF THE LATEST CLINICAL TRIALS - REVIEW - Patrycja Szczygielska; Sylwia Hejna; Weronika Smutkiewicz; Weronika Teterycz; Wiktoria Goździejewska; Łukasz Jaworek; Gabriela Zimka; Krystian Bjorgen; Lilianna Jasińska; Magdalena Roman (International Journal of Innovative Technologies in Social Science, 2026)
In recent years, there has been rapid progress in cell therapies based on modified T cells, particularly CAR-T and CAR-Treg technologies, which show promise in the treatment of severe autoimmune diseases. Systemic lupus erythematosus (SLE) and systemic sclerosis (SSc) are diseases characterized by profound dysregulation of the immune system, leading to chronic inflammation and multiorgan damage. Despite the use of conventional immunosuppressive therapies, a significant proportion of patients remain refractory to treatment, justifying the search for new therapeutic strategies. The aim of this review is to analyze the efficacy and safety of CAR-T and CAR-Treg cells in the context of the latest clinical trials published between 2024 and 2026. Particular attention was paid to the immunological mechanisms underlying the action of these therapies, their ability to “reset” the immune system, and their impact on long-term disease remission. Available clinical data indicate that B-cell-targeted CAR-T therapy (e.g., CD19) can lead to deep and long-lasting remission in patients with refractory SLE through the elimination of autoreactive cell populations and the restoration of the immune repertoire (Wang et al., 2025; Xu et al., 2025). At the same time, new strategies utilizing CAR-Treg cells are emerging, aimed at restoring immune tolerance without systemic immunosuppression. Despite promising results, this therapy is associated with potential risks, such as cytokine release syndrome or neurotoxicity, although in recent studies their incidence appears to be limited (Zhou et al., 2024; Wang et al., 2025). In summary, CAR-T and CAR-Treg therapies represent a breakthrough in the treatment of severe autoimmune diseases; however, their widespread use requires further research on safety, accessibility, and the optimization of therapeutic protocols.